Peran Digital Forensik Dalam Pengumpulan Bukti Pada Kasus Judi Online di Kabupaten Demak - Tazkia Asshiva Maryam; Marsya Arviela Maharani; Tigor Akhmad Fahrezi; Andriyanto Adhi Nugroho (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2024)
This research aims to maximize the role of digital forensics in the discovery of electronic evidence and to understand the forms of accountability for online gambling offenders in Demak Regency. The method used in this research is normative juridical and descriptive-analytical. The findings from this research include the following: First, online gambling is a criminal act committed using electronic devices, thus requiring electronic data for its investigation. In this context, the role of digital forensics is essential to find and collect evidence to uncover online gambling cases in Demak Regency. The use of digital forensics in discovering electronic evidence in online gambling cases in Demak Regency can be conducted using the Integrated Digital Forensics Investigation Framework (IDFIF). This method consists of four stages: preparation, crime scene investigation, laboratory examination, and reporting. Second, the form of accountability for online gambling offenders is outlined in Article 27 paragraph (2) of Law No. 19/2016 on Amendments to Law No. 11/2008 on Electronic Information and Transactions. This article stipulates that any person who intentionally and without authority distributes or transmits electronic documents containing gambling content. The criminal penalties for violations of Article 27 paragraph (2) are specified in Article 45 paragraph (2) of Law No. 19/2016, which is a maximum imprisonment of 6 years and/or a maximum fine of Rp. 1,000,000,000.00.